The given functions are: \[ f(x) = 8x - 4, \quad g(x) = 4x - 9 \]
To find \( (f - g)(x) \), subtract \( g(x) \) from \( f(x) \): \[ (f - g)(x) = f(x) - g(x) = (8x - 4) - (4x - 9) \]
Remove the parentheses and combine like terms: \[ (f - g)(x) = 8x - 4 - 4x + 9 = (8x - 4x) + (-4 + 9) = 4x + 5 \]
\(\boxed{4x + 5}\)
Oops, Image-based questions are not yet availableUse Solvely.ai for full features.
Failed. You've reached the daily limit for free usage.Please come back tomorrow or visit Solvely.ai for additional homework help.